PENGARUH KEPEMIMPINAN TERHADAP DISIPLIN DAN KINERJA TENAGA PENDIDIK (STUDI KASUS DI PASRAMAN WIDYA BHAKTI KOTA PALANGKA RAYA) - Made Gede Ardika (Tampung Penyang, 2020)
The role of a leader in an organization becomes an urgent and very important thing to do to improve the decrease in the attendance of educators so that it will have an impact on the performance of educators. The influence of a leader is very important to encourage educators to be more disciplined and improve performance, of course, with policies and decisions made so that educators can carry out the tasks assigned to educators in order to realize the goals to be achieved by Pasraman Widya Bhakti Palangka Raya City, namely the realization of discipline from the discipline all components to form a strong and sturdy personality and improve the quality of education that is educative and insightful. Based on this background, this study was conducted with the focus of the study on three aspects of the problem, namely the form of leadership influence, the effect of leadership influence and the implications of leadership influence on the discipline and performance of educators in Pasraman Widya Bhakti, Palangka Raya City. This study uses a qualitative approach and to analyze the results of the study used the theory of structural functionalism, management theory and supporting theory. Based on the analysis and analysis method can be delivered as follows, namely the form of leadership influence, leadership influence function and the implications of leadership influence on the discipline and performance of educators in Pasraman Widya Bhakti Palangka Raya City.